Helppppppppppppppppppppppppp
![Helppppppppppppppppppppppppp class=](https://us-static.z-dn.net/files/d26/ef426400a97966eb1f5426002796c97e.png)
Answer:
with the process for the first one you could do the others.
[tex]x=5[/tex] and [tex]y=2[/tex]
Step-by-step explanation:
We have two linear equations
[tex]4x+3y=26[/tex] and [tex]\frac{y}{3}=\frac{x}{3}-1[/tex]
From the second equation we can find y then
[tex]y=3(\frac{x}{3}-1)[/tex]
[tex]y=3\frac{x}{3}-3[/tex]
[tex]y=x-3[/tex]
Now we use this expression of y in the first equation
[tex]4x+3y=26[/tex]
[tex]4x+3(x-3)=26[/tex]
[tex]4x+3x-9=26[/tex]
[tex]7x=26+9[/tex]
[tex]x=\frac{35}{7}[/tex]
[tex]x=5[/tex]
Now que can find the value of y
[tex]y=x-3[/tex]
[tex]y=5-3[/tex]
[tex]y=2[/tex]